Measuring the Social Impact of Digital Services: A Case of St. Petersburg, Russia - Bolgov, Radomir; Filatova, Olga; Volkovskii, Daniil (Conference on Digital Government Research, 2025)
The paper presents the results of using automated tools to study the dissemination of information in media, social networks and instant messengers, as well as the comments to mobile applications, allowing to search for information by keywords. The cases analysed are the Unified Ecosystem of Urban Services "Digital Petersburg" and its flagship application "I Live Here", as well as the mobile application "Unified Card of St. Petersburg Resident" as part of a study on the social impact of digital services. The data obtained indicate on low awareness of citizens about digital public services. At the same time, we can talk about the high demand among citizens for the "Unified Card of St. Petersburg Resident" service, where, unlike the first case, there is active feedback from the authorities and work to eliminate the shortcomings of the service.